2021
DOI: 10.1039/d1nj01049b
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric bis-salicylaldiminato binuclear titanium complexes for ethylene polymerization and copolymerization

Abstract: Polyolefins with high molecular weight and broad molecular weight distribution have attracted great attention due to their ease of processing and wide applications. In this paper, methylene-bridged asymmetric disalicylaldimine ligands...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…[1,2] Some recent examples of successful application of binuclear titanium complexes for ethylene (co)polymerization are given in previous studies. [3][4][5][6][7] It was previously shown that binuclear and hexanuclear titanium complexes stabilized by a tetradentate derivative of 2-hydroxymethylphenol showed significantly higher catalytic activity and thermal stability in ethylene polymerization in comparison to mononuclear analogue. [8,9] One of the most important factors in the design of binuclear and polynuclear olefin polymerization precatalysts is the distance between the metal centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Some recent examples of successful application of binuclear titanium complexes for ethylene (co)polymerization are given in previous studies. [3][4][5][6][7] It was previously shown that binuclear and hexanuclear titanium complexes stabilized by a tetradentate derivative of 2-hydroxymethylphenol showed significantly higher catalytic activity and thermal stability in ethylene polymerization in comparison to mononuclear analogue. [8,9] One of the most important factors in the design of binuclear and polynuclear olefin polymerization precatalysts is the distance between the metal centers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] Some recent examples of successful application of binuclear titanium complexes for ethylene (co)polymerization are given in previous studies. [ 3–7 ]…”
Section: Introductionmentioning
confidence: 99%